The Relevance of the Standard of Maintenance in the Classical Book of Turats Syafi'iyyah and the Local Wisdom of the Javanese People to Family Harmony - Jufri Aldhi Wijaya; Ita Rahmania Kusumawati (Jurnal Indonesia Sosial Teknologi, 2024)
Marriage is a way chosen by Allah as a way for humans to carry on life. Maintaining the permanence of a marriage with harmony, love, and affection is not easy. Because in marriage some rights and obligations must be fulfilled between husband and wife. The type of research used by the author in this journal is field research. Meanwhile, the approach used in this study is qualitative. This research is descriptive. The results of this study show that according to the opinion of the people of Bancong Village, Wonoasri District, Madiun Regency, the standardization of the provision of wife support is the size or size of the maintenance that the husband gives to his wife every month and the amount cannot be determined every month because it depends on the income earned by the husband in that month and the one who regulates the needs of the family is the wife while the husband must earn a living to be sufficient family needs. Meanwhile, a harmonious household is the giving of a husband's affection as a whole to the whole family and there is a balance between the rights and obligations of the married couple so that the family is always in a peaceful and peaceful state without any gap between each other. Meanwhile, regarding the relevance of the standardization of alimony, according to the people of Bancong Village, Wonoasri District, Madiun Regency, it cannot be influenced because the local community is not so concerned about the standardization rules or the size of alimony, the important thing is that the alimony can meet the needs of the family.